The Rumor about Pan Thaiism in Laos in the Late 1960s during the Cold War - Choosiri, Seubsaisiam (CRMA Journal of Humanities and Social Sciences, 2024)
This article aims to examine the Pan Thaiism rumors that emerged among the progressive Thai intellectuals in the context of the 2510s B.E. (1967–1976 C.E.) during the Cold War, particularly the origins of the rumors and the amount of factual evidence and official documents supporting them. Through historical research, it was found that the Thai government secretly sent Thai mercenaries to fight against the left-wing faction in Laos and attempted to conceal it from the public. This secrecy led to ambiguity and the eventual proliferation of “rumors,” possibly including that about Pan Thaiism, the Thai plan to annex Laos by the secret troops, among the contemporary progressive Thai intellectuals. In fact, so far there have been no Thai official documents that confirm these speculations.